Design of a Low-Cost Microphone Array for Portable Multi-Platform Applications - Roman-Asenjo, P (Elsevier Ltd, 2025)
Acoustic imaging analysis of noise sources is a widespread method to obtain source spatial positioning and parameters like sound pressure. The challenge is to record audio from multiple microphones simultaneously and optionally capture color images from a camera for final overlapped sound localization display. We propose a multiple hardware component interconnection device, with necessary and optional parts available from different retailers and minimal printed circuit board designs. The setup is based on a 3D-printed base that can be modified to achieve different portable microphone array configurations. The final product is USB 2.0 compliant and can be connected to multiple computers and operating system, as well as various development boards. The simple script provided allows recording 16-channel files at 48 kHz and 32 bits, alongside optional colored point clouds from a depth camera. Measurements taken in an anechoic chamber and post-processing with inverse methods result in holographic reconstruction of noise sources surface parameters and a sound power approximation. © 2025 The Authors